Fe-Ni alloy foil, method for producing Fe-Ni alloy foil, and component
In the manufacturing process of Fe-Ni alloy foil, the vacancy in the alloy ingot is uniformly dispersed by hot powder metallurgy method, and the deformation problem caused by residual stress unevenness during the rolling process is solved, and an alloy with a plate thickness of less than 50μm is realized The foil is suppressed to improve quality and technical performance.
Patent Information
- Application Number
- CN202380050901.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-12
- Publication Date
- 2025-02-18
AI Technical Summary
In the manufacturing process of Fe-Ni alloy foil, especially during the rolling process, uneven residual stress is easily generated, resulting in deformation such as edge waves, intermediate ripples, warping, etc., especially when the plate thickness is less than 50μm, these deformations are present. Revealing has become an important issue in quality and technology.
By dispersing vacant positions evenly in alloy ingots, using hot powder metallurgy (such as HIP method) to manufacture alloy ingots, and controlling the rolling conditions during the rolling process, ensuring uniform distribution of vacant positions, thereby reducing residual stress unevenness and suppressing deformation .
By uniformly dispersing the vacancy in the alloy foil, deformation such as edge waves, intermediate ripples, warping and other deformations can be effectively suppressed, and the quality and technical performance of the Fe-Ni alloy foil are improved, especially when the plate thickness is less than 50 μm.
Smart Images

Figure CN119487229A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an Fe-Ni metal foil, a method for producing the Fe-Ni metal foil, and a component using the Fe-Ni alloy foil. Background Art
[0002] With the miniaturization and high-density assembly of electronic devices, it is required that the size of each electronic component constituting the electronic device be reduced or lightweight. For example, aluminum foil (aluminum foil) or stainless steel foil containing Fe-Ni alloy foil (stainless steel foil) is applied as a shell for a secondary battery. In order to make the secondary battery lighter and thinner, the thickness of the shell plate is also sought to be thinner, but it is also required to ensure that the strength is maintained. Therefore, the replacement of the previous aluminum foil with stainless steel foil has been promoted to maintain strength and reduce thickness (for example, Patent Document 1).
[0003] In addition, not only the components used in electronic devices themselves, but also the materials or components indispensable for manufacturing electronic devices are required to be thinner. For example, Fe-Ni alloy foil with good etching properties and thermal expansion properties is used for metal masks indispensable for manufacturing organic light-emitting diodes (OLEDs), but with the increase in pixel density, the thickness is also required to be thinner (for example, Patent Document 2).
[0004] In response to the demand for thinner Fe—Ni alloy foils, Fe—Ni alloy foils with a thickness of 100 μm or less are in circulation, and there is a demand for Fe—Ni alloy foils with a thickness of less than 50 μm.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2015 / 122523
[0008] Patent Document 2: International Publication No. 2020 / 067537 Summary of the invention
[0009] Technical problem to be solved by the invention
[0010] When the thickness of Fe-Ni alloy foil is reduced, uneven residual stress is easily generated during its manufacturing process (especially rolling). In order to remove the residual stress, stress relief annealing is performed after rolling, but the residual stress cannot be removed in the end, which becomes the cause of deformation such as edge waves, middle corrugation, and warping. This deformation becomes a problem in the quality of Fe-Ni alloy foil. Especially when the plate thickness is less than 50μm, these deformations appear and become important problems in quality and technology.
[0011] Therefore, the present invention aims to suppress deformation such as edge waves, middle waves, and warping in Fe-Ni alloy foil having a thickness of 50 μm or less, and aims to obtain Fe-Ni alloy foil (hereinafter sometimes simply referred to as alloy foil) with such deformation suppressed.
[0012] Technical means for solving technical problems
[0013] The inventors of the present invention have continued intensive research and development to achieve the above-mentioned objects and have obtained the following findings.
[0014] (a) The cause of deformations such as edge waves, middle corrugations, and warping is the deformation non-uniformity in the alloy foil, and the deformation non-uniformity is believed to be caused by the non-uniform residual stress in the alloy foil. It is known that the residual stress is added during the manufacturing process of the alloy foil, especially by rolling. Through rolling, dislocations or vacancies in the alloy plate (there is no clear standard for the thickness of alloy foil and alloy plate, but for example, a plate with a thickness of more than 100μm can be called an alloy plate, and a plate with a thickness of less than 100μm can be called an alloy foil. In the following, a plate-like Fe-Ni alloy with a thickness of more than 100μm before being rolled to become a thinned alloy foil is sometimes referred to as an Fe-Ni alloy plate, or simply an alloy plate.) move and deform. Dislocations themselves are generated by the movement and combination of vacancies. Therefore, the inventors focused on the behavior of vacancies in the alloy plate. In addition, the vacancies in the present invention are not defects such as shrinkage holes or gas vacancies during solidification in cast products, but represent atomic vacancies or point defects.
[0015] (ii) It is assumed that if the vacancies in the alloy plate are uniformly dispersed, the movement and combination of the vacancies during rolling of the alloy plate become uniform, and the deformation behavior in the alloy plate becomes uniform. Therefore, for example, an alloy ingot is manufactured by hot powder metallurgy (HIP method, etc.), and it is rolled to obtain an alloy foil, and the deformation behavior is evaluated. As a result, it is confirmed that edge waves or intermediate corrugations and warping are suppressed. Thus, it is confirmed that an alloy foil with suppressed deformation is obtained by rolling an alloy ingot in which the vacancies are uniformly dispersed.
[0016] (III) As an indicator of the uniform dispersion of vacancies in the rolled plate, the vacancy positron annihilation lifetime (PAL) is considered. PAL is a comprehensive indicator of the number of vacancies or the size of vacancies. The larger the vacancy size, the longer the PAL; the more vacancies there are, the greater the intensity detected. When the number of vacancies increases, the vacancies combine with each other, and eventually the vacancy size increases. The inventors found through experiments that the larger the PAL, the more the deformation is suppressed.
[0017] (iv) According to experiments in Fe-Ni alloy foil, it was confirmed that if PAL is 0.150ns (nanoseconds: nanoseconds) or more, the deformation is more suppressed compared to previous alloy foils. In addition, it was confirmed that most existing alloy foils have a PAL of less than 0.150ns. This is believed to be due to the fact that the existing alloy ingots are manufactured by the melting method. In the case of the melting method, it is believed that vacancies gather during the solidification process, and edge dislocations are easily generated, which damages the uniformity of vacancies in the alloy ingot after solidification.
[0018] The present invention has been obtained based on the above findings, and its gist is as follows. [1]
[0020] An Fe-Ni alloy foil, characterized in that:
[0021] The composition is expressed in mass %
[0022] C: 0~0.030%,
[0023] Si: 0-0.21%,
[0024] Mn: 0~0.30%,
[0025] Ni: 30.0~60.0%,
[0026] Co: 0-5.00%,
[0027] P: 0.01% or less,
[0028] S: 0.01% or less, and
[0029] The rest is Fe and impurities.
[0030] The plate thickness is 50 μm or less, and the positron annihilation lifetime (PAL) is 0.150 ns or more.
[0031] [2] The Fe-Ni alloy foil as described in [1],
[0032] The positron annihilation lifetime (PAL) is 0.150ns to 0.200ns.
[0033] [3] The Fe—Ni alloy foil according to [1] or [2], wherein the thickness is 20 μm or less.
[0034] [4] A method for producing an Fe—Ni alloy foil, the method for producing an Fe—Ni alloy foil according to any one of [1] to [3], comprising:
[0035] A process for preparing Fe-Ni alloy powder;
[0036] A Fe-Ni alloy ingot manufacturing process of manufacturing the Fe-Ni alloy powder into a Fe-Ni alloy ingot by a HIP method; and
[0037] a rolling process of rolling the Fe-Ni alloy ingot,
[0038] The composition of the Fe-Ni alloy powder is expressed in mass %,
[0039] C: 0~0.030%,
[0040] Si: 0-0.21%,
[0041] Mn: 0~0.30%,
[0042] Ni: 30.0~60.0%,
[0043] Co: 0-5.00%,
[0044] P: 0.01% or less,
[0045] S: 0.01% or less, and
[0046] The remainder is Fe and impurities.
[0047] [5] The method for producing the Fe-Ni alloy foil according to [4],
[0048] Furthermore, the rolling process includes at least one annealing process between each rolling pass or after the final rolling.
[0049] [6] A component comprising the Fe—Ni alloy foil according to any one of [1] to [3].
[0050] Effects of the Invention
[0051] According to the present invention, it is possible to obtain an Fe—Ni alloy foil in which deformations such as edge waves, intermediate waves, and warping are suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a diagram showing an example of the relationship between PAL and deformation amount in Fe—Ni alloy foil.
[0053] Figure 2 It is a diagram showing an outline of the vertical direction suspension test.
[0054] Figure 3 This is a conceptual diagram for explaining an example of a method for measuring a gap generated between a test piece and a vertical plane in a vertical direction suspension test. DETAILED DESCRIPTION
[0055] The Fe-Ni alloy foil of the present invention is described in detail below. Unless otherwise specified, "%" related to a component represents mass % in steel. When there is no particular lower limit or when the lower limit is 0%, it includes the case where no content (0%) is included.
[0056] [Positron annihilation lifetime (PAL)]
[0057] Positron annihilation lifetime (PAL: Positron Annihilation Lifetime) is an indicator used to evaluate lattice defects including vacancies in materials such as metal materials or polymer materials. It is sometimes also called average positron annihilation lifetime. PAL can evaluate the types of lattice defects. PAL is a comprehensive indicator such as the number of vacancies or the size of vacancies in the material. The so-called vacancies in the present invention are not the type defects of shrinkage holes or gas vacancies during solidification in the casting, but represent atomic vacancies or point defects. Although the detailed description of PAL is omitted here, the larger the vacancy size, the longer the PAL. On the other hand, the more vacancies there are, the greater the relative intensity detected (the number of counts of gamma rays emitted when positrons are annihilated, which is equivalent to the probability of existence); when the number of vacancies increases, vacancies combine with each other, and finally the vacancy size becomes larger, and the PAL becomes longer.
[0058] The positron annihilation lifetime (PAL) can be measured by a PAL measuring device. As the PAL measuring device, for example, a commercially available device such as a positron annihilation lifetime measuring device manufactured by Techno-AP can be used. The inventors of the invention used a positron annihilation lifetime measuring device manufactured by Techno-AP. 22 Na was evaluated as a positron ray source.
[0059] When evaluating PAL, the Fe-Ni alloy foil to be evaluated is cut into 10 mm squares, and two groups of three overlapping pieces are prepared. The positron beam source is clamped by the three overlapping Fe-Ni alloy foils, and the foil is wrapped and fixed with aluminum foil to make a PAL measurement sample. The prepared measurement sample is set in the measurement device to measure the positron annihilation lifetime (PAL). The data analysis software can also use the software attached to the measurement device (for example, PALSfit3 developed by DENMARK University of Technology). When measuring, the influence of the lifetime of the Kapton film (0.3800ps) or the lifetime of the epoxy resin (1.9044ps) is taken into account, so their lifetimes can be fixed for analysis.
[0060] The material (melting material) manufactured by the existing smelting method is equivalent to having no vacancies, and the main body of the lattice defects is dislocation. Moreover, in the case of the smelting material, the dislocation is not uniformly introduced as a whole during the solidification process. In short, the state of the dislocation is different on the surface and the center of the solidified alloy ingot. In the case where the main body of the defect is a dislocation, when the stress concentration caused by processing exceeds the yield stress, dislocation occurs and plastic deformation is performed, thereby stress relaxation, but at the same time, work hardening is caused by the interaction between dislocations. Therefore, when dislocations are unevenly introduced into the material, stress relaxation occurs locally, and the residual stress tends to become uneven.
[0061] On the other hand, in thermal powder metallurgy methods such as HIP, shrinkage pores or gas vacancies can be eliminated, but atomic vacancies cannot be eliminated. Materials manufactured by thermal powder metallurgy (thermal powder metallurgy materials) are believed to have multiple vacancies uniformly generated in the material because the powder is isotropically compressed and sintered at high temperatures. In thermal powder metallurgy, the vacancies diffuse, so that the necks between the particles grow and sintering progresses. That is, unlike materials based on the previous melting method, materials manufactured by thermal powder metallurgy become microstructures with vacancies.
[0062] Vacancies are used in the rising movement of edge dislocations, and have the function of arranging vacancies to form dislocations. Therefore, the organization of hot powder metallurgy materials with long positron annihilation lifetime and large proportion of vacancies (large number) is considered to be easy to form dislocations by vacancy movement, and dislocations can move while absorbing many vacancies, so it becomes a relatively easy organization for dislocations to move. The ease of formation or movement of such dislocations will affect the stress relaxation of the material. In addition, the residual vacancies not used in the dislocations act in the same way as solid solution strengthening, which contributes to the strength of the base. Therefore, if vacancies are uniformly introduced into the material, the vacancies are easy to move due to rolling, etc., so even relatively light rolling loads are easy to deform. In addition, it is believed that because stress relaxation is uniformly performed in the material, the residual stress becomes uniform, so deformation (warping or lateral bending, etc.) can be suppressed. On the other hand, the molten material has a short positron annihilation lifetime and a small proportion of vacancies (small number), so it is difficult for edge dislocations to rise and dislocations are difficult to move. That is, dislocations in the molten material are unevenly distributed and difficult to move, so residual stress is uneven and shape defects are likely to occur.
[0063] The inventors of the present invention have confirmed through experiments that if it is a conventional smelting material, the PAL will not be 0.150ns or more, but if it is a hot powder metallurgy material, it is 0.150ns or more. That is, it was confirmed that in the case of a material in which the defects are mainly dislocations, such as conventional smelting materials, the PAL is less than 0.150ns, and in the case of a material in which point defects such as vacancies are mainly, such as hot powder metallurgy materials, the PAL is 0.150ns or more. Therefore, a PAL of 0.150ns or more is considered to indicate a structure in which the lattice defects are mainly point defects such as vacancies. That is, PAL 0.150ns is considered to be the boundary of the microstructure that changes from dislocations to vacancies.
[0064] [Deformation]
[0065] The deformation of the Fe-Ni alloy foil, such as edge waves, middle corrugations, and warping, occurs in a complex manner, so it is difficult to evaluate each deformation individually. Therefore, in order to comprehensively evaluate the deformation of the alloy foil, it is considered that when the alloy foil is suspended vertically, the maximum value of the deformation of the alloy foil relative to the vertical direction can be used as the deformation of the alloy foil.
[0066] The inventors of the present invention adopted the following test method to obtain the deformation evaluation based on the vertical suspension test. That is, the alloy foil is cut into a rectangle of, for example, 40 mm wide and 250 mm long as a test piece, and it is suspended on a vertical platform (a platform having a plane (vertical plane) parallel to the vertical direction), and the gap between the vertical plane and the test piece is measured, and its maximum value is used as the deformation for evaluation. Usually, edge waves and intermediate corrugations are generated along the rolling direction, so the long side of the test piece is set as the rolling direction. In addition, when manufacturing the alloy foil, there is a situation where it is coiled in a coil shape. In order to eliminate the winding inertia generated at this time, a certain tension is added. For example, if the test piece is less than 50 μm thick and 40 mm wide, a weight of 100 g is hung at the lower end of the test piece to generate tension. The method for measuring the gap between the test piece and the vertical plane is not particularly limited, but can be measured by a feeler gauge or laser length measurement, image analysis based on photo shooting, etc.
[0067] [Positron annihilation lifetime (PAL) ≧ 0.150ns]
[0068] Figure 1 1 shows an example of the relationship between the PAL and the deformation amount of the Fe—Ni alloy foil shown in the examples. Figure 1 This is a graph showing the relationship between PAL and deformation using a 30 μm thick Fe-Ni alloy foil. Figure 1As shown, it can be confirmed that the deformation amount is strongly correlated with PAL, and the deformation amount decreases when PAL increases. In other words, it is confirmed that the deformation of the alloy foil can be suppressed by changing the type of lattice defects from dislocation-dominated (PAL less than 0.150ns) to vacancy-dominated (PAL greater than 0.150ns).
[0069] That is, it was confirmed that: by setting PAL to 0.150ns or more, an Fe-Ni alloy with a microstructure dominated by vacancies is obtained, the inhomogeneity of residual stress caused by rolling is reduced, and finally an Fe-Ni alloy foil with suppressed deformation is obtained. Since the longer the PAL, the smaller the deformation, the longer the PAL is. Therefore, the lower limit of PAL is preferably 0.151ns, 0.152ns, 0.153ns, 0.154ns, 0.155ns, 0.156ns, 0.157ns, 0.158ns, 0.159ns, 0.160ns, 0.161ns, 0.162ns, 0.163ns, 0.164ns, or 0.165ns.
[0070] On the other hand, the longer the PAL is, the smaller the deformation is. However, when the PAL grows to a certain extent, there will be large vacancies, which may become the starting point of destruction. According to the experiments of the inventors of the present invention, there is no PAL measured value exceeding 0.200ns in practical thermal powder metallurgy materials. Therefore, the upper limit value of PAL does not need to be specifically limited, but when the upper limit value is set, it is set to 0.200ns, preferably 0.198ns, 0.196ns, 0.194ns, 0.192ns, 0.190ns, 0.188ns, 0.186ns, 0.184ns, 0.182ns, or 0.180ns.
[0071] [Composition of Fe-Ni alloy foil]
[0072] The composition of the Fe-Ni alloy foil will be described. As described above, "%" related to a composition means mass % in steel unless otherwise specified. When there is no particular lower limit or when the lower limit is 0%, it includes the case where no content (0%) is included.
[0073] C: 0~0.030%,
[0074] Carbon (C) increases the strength of the alloy foil. However, if C is contained excessively, inclusions caused by carbides of the alloy increase. Therefore, the C content can be set to 0.030% or less. Preferably, it can be set to 0.028%, 0.026%, 0.024%, 0.022%, or 0.020%.
[0075] Si: 0~0.21%
[0076] Silicon (Si) increases the thermal expansion coefficient of the alloy. Fe-Ni alloy foil was originally expected to be an alloy with a low thermal expansion coefficient. Although it also depends on its use, it is also used in a temperature environment of about 200°C. Furthermore, when the Si content is too high, the strength becomes too high and the processability of the alloy decreases. Therefore, from the perspective of suppressing thermal expansion or processability, the Si content can be set to 0.21% or less. It is preferably set to less than 0.20%, less than 0.18%, 0.16%, 0.14%, 0.12%, or less than 0.10%.
[0077] Mn: 0~0.30%,
[0078] In order to avoid the formation of spinel, manganese (Mn) is used as a deoxidizer instead of Mg and Al. However, if the Mn content is too high, it will segregate to the grain boundary, promote grain boundary destruction, and the hydrogen embrittlement resistance will deteriorate. Therefore, the Mn content can be set to 0.30% or less. The preferred range of the Mn content is set to 0.28% or less, 0.26% or less, 0.24% or less, 0.22% or less, 0.20% or less, 0.18% or less, or 0.16% or less.
[0079] Ni: 30.0~60.0%,
[0080] Nickel (Ni) is the main component for suppressing the thermal expansion coefficient of the alloy to a low level, and if the Ni content is too low, the body-centered cubic (bcc) structure increases and the behavior of dislocations changes. Therefore, the Ni content can be set to 30.0% or more. On the other hand, if the Ni content is too high, bainite structure is easily generated in the alloy after hot working (hot rolling or hot forging). Therefore, the Ni content can be set to 60.0% or less. The preferred range of Ni content is 31.0% or more, 31.5% or more, 32.0% or more, 32.5% or more, 33.0% or more, 33.5% or more, 34.0% or more, 34.5% or more, 35.0% or more, 35.2% or more, or 35.4% or more on the lower limit side, and 59.0% or less, 58.0% or less, 57.0% or less, 56.0% or less, 55.0% or less, 54.0% or less, 56.5% or less, 57.5% or less, 58.5% or less, 59.0 ... 3.0% or less, 52.0% or less, 51.0% or less, 50.0% or less, 49.0% or less, 48.0% or less, 47.0% or less, 46.0% or less, 45.0% or less, 44.0% or less, 43.0% or less, 42.0% or less, 41.0% or less, 40.0% or less, 39.5% or less, 39.0% or less, 38.5% or less, 38.0% or less, 37.5% or less, or 37.0% or less.
[0081] Co: 0~5.00%
[0082] It is a component that can further reduce the thermal expansion coefficient of the alloy when its addition amount is increased in association with the Ni amount. However, since it is a very expensive element, the upper limit of the Co content can be set to 5.00%. Preferably, it can be set to 4.50% or less, 4.00% or less, 3.50% or less, 3.00% or less, 2.50% or less, 2.00% or less, 1.50% or less, or 1.00% or less.
[0083] [Impurities]
[0084] The remainder other than the above elements is Fe (iron) and impurities. Impurities are elements that are contained unintentionally during the manufacturing process. In particular, impurities include P, S, etc. The content of P or S is preferably limited to the following range.
[0085] P: 0.010% or less,
[0086] P segregates to the grain boundaries during solidification, increasing the solidification crack sensitivity. Therefore, the P content is preferably as low as possible. Therefore, the P content is limited to 0.010% or less. It is preferably set to 0.005% or less, or 0.003% or less. The lower limit of the P content is 0%, but if it is excessively reduced, the manufacturing cost will increase, so it can be 0.001% or more in reality.
[0087] S: 0.010% or less,
[0088] S segregates to the grain boundaries during solidification, increasing the solidification crack sensitivity. Therefore, the S content is preferably as low as possible. Therefore, the S content is limited to 0.010% or less. It is preferably set to 0.005% or less, or 0.002% or less. The lower limit of the S content is 0%, but excessive reduction will increase the manufacturing cost, so it is practical to be 0.001% or more.
[0089] As impurities, other elements may be contained as impurities within a range not impairing the effects of the present invention, for example, Cr, Al, Cu, Nb, Mo, Ti, Mg, Ca, Sn, V, W, Zr, B, Bi, etc.
[0090] [Plate thickness]
[0091] The thickness of the Fe-Ni alloy foil is not particularly limited. An alloy plate with a thickness of less than 100 μm is called an alloy foil, but it can also be applied to an alloy plate with a thickness of more than 100 μm. However, generally, the thinner the plate thickness, the easier it is to cause deformations such as edge waves, intermediate corrugations, and warping. Therefore, it is more effective to apply the present invention to Fe-Ni alloy foils with a thickness of less than 50 μm. The thinner the plate thickness, the more the effect of the present invention can be exerted, so it is preferably less than 45 μm, less than 40 μm, less than 35 μm, less than 30 μm, less than 25 μm, less than 20 μm, less than 15 μm, less than 10 μm, or less than 5 μm. The lower limit of the plate thickness is not particularly limited, but from the perspective of industrial manufacturing feasibility, the plate thickness can also be greater than 1.0 μm.
[0092] [Manufacturing method]
[0093] The manufacturing method of the Fe-Ni alloy foil of the present invention is not particularly limited. However, the life of the PAL can be prolonged by mainly spending effort in the manufacturing process, rolling process, and annealing process of the alloy ingot. The method is described below. In addition, the Fe-Ni alloy foil of the present invention is not limited to the manufacturing method described here.
[0094] [Fe-Ni alloy ingot manufacturing process]
[0095] The manufacturing process of the so-called Fe-Ni alloy ingot is a process of obtaining an ingot (steel sheet, slab, etc.) of an Fe-Ni alloy having a specified composition. For example, there is a method of refining a molten Fe-Ni alloy to solidify it, which is called a smelting method. In addition, for example, there is a method of combining metal powders of a specified composition and solid-phase bonding under high temperature and high pressure, such as HIP (Hot Isostatic Press), which is called a hot powder metallurgy method.
[0096] As mentioned above, the alloy ingot (melting alloy ingot) of the molten material manufactured by the existing smelting method is equivalent to having no vacancies, and the main body of the lattice defects is dislocation. In addition, in the case of the molten material, dislocations are not introduced uniformly as a whole during the solidification process. In short, the way of introducing dislocations is different on the surface and the center of the molten alloy ingot. In the case where the main body of the defect is dislocation, when the stress concentration caused by processing exceeds the yield stress, dislocations occur and plastic deformation occurs, thereby relieving stress. Therefore, when dislocations are unevenly introduced into the molten alloy in the material, stress relief occurs locally, and residual stress is prone to unevenness.
[0097] On the other hand, in thermal powder metallurgy methods such as the HIP method, although shrinkage pores or gas vacancies can be eliminated, atomic vacancies cannot be eliminated. Materials manufactured by thermal powder metallurgy (thermal powder metallurgy materials) are believed to be isotropically compressed and sintered at high temperatures, so that multiple vacancies are uniformly generated in the material. In the thermal powder metallurgy method, the vacancies diffuse, so that the necks between the particles grow and sintering progresses. That is, unlike smelting materials, materials manufactured by thermal powder metallurgy are microstructures with vacancies. Therefore, compared to existing smelting methods, thermal powder metallurgy methods such as the HIP method uniformly generate multiple vacancies, and alloy ingots with extended PAL life can be obtained.
[0098] [Fe-Ni alloy powder preparation process]
[0099] In the case of manufacturing by hot powder metallurgy, the manufacturing method is not particularly limited. For example, the HIP method used in the past can be applied. In order to uniformly generate vacancies in the manufactured alloy ingot, the metal powder used as the raw material of the HIP method is preferably fine particles. For example, the particle size of the metal powder is set to 500μm or less, 400μm or less, 300μm or less, 200μm or less, or 100μm or less. The manufacturing method of the metal powder is also not particularly limited. The alloy powder can be obtained by applying the atomization method to the molten liquid adjusted to a specified component composition by the existing refining method. The refining method at this time is also not particularly limited. It can also be carried out by a vacuum induction heating furnace at the laboratory level. In order to reduce the carbon content, gas components, and metal inclusions, AOD (Argon-Oxygen-Decarburization: Argon Oxygen Decarburization) method, VOD (Vacuum-Oxygen-Decarburization: Vacuum Oxygen Decarburization) method, V-AOD method, etc. can be applied.
[0100] The prepared alloy powder is placed in a metal container and subjected to HIP treatment to obtain the desired alloy ingot. If a hot powder metallurgy method such as HIP is used, a near net shape alloy ingot close to the final product shape can be obtained, and the subsequent processing steps (rolling or forging, etc.) can be omitted.
[0101] [Rolling process]
[0102] The obtained Fe-Ni alloy ingot is hot-rolled or cold-rolled to obtain alloy foil. Generally speaking, the Fe-Ni alloy ingot can be hot-rolled to form an Fe-Ni alloy plate with a thickness of less than 1 mm, and then the alloy foil with the desired thickness can be obtained by cold rolling. Both hot rolling and cold rolling can adopt existing manufacturing methods. However, in order to extend the life of PAL, it is preferred that the total reduction rate of each pass of cold rolling is not too large. This is because when the total reduction rate of cold rolling is too large, it becomes a rolling structure with high dislocation density due to strain accumulation due to rolling, and vacancies are easily consumed. In the range where the work hardening ability is not reduced, it is preferred to reduce the total reduction rate of cold rolling to achieve a process design such as gentle rolling.
[0103] [Annealing process]
[0104] When manufacturing Fe-Ni alloy foil, when the plate thickness becomes thinner (for example, the plate thickness is less than 100 μm), at least one annealing is performed between rolling passes (it can also be between each rolling pass or between several passes) in the rolling process (especially cold rolling) or after the final rolling (the rolling pass is called intermediate annealing, and the final annealing is called final annealing after the final rolling). After annealing, dislocations and vacancies are temporarily reduced together to form a uniform recrystallized structure. In the case of intermediate annealing, dislocations are introduced again due to the subsequent rolling, but the dislocation density is not high compared to the unannealed rolling structure, so dislocations are easy to move. Due to the collision of dislocations, vacancies are generated and the dislocation density is also increased. This ultimately leads to a longer life of the PAL. Therefore, it is preferred to perform annealing, and it is particularly preferred to perform intermediate annealing between rolling.
[0105] As mentioned above, dislocations can be eliminated by annealing, but the elimination of dislocations does not progress without recrystallization. Therefore, it is expected to perform annealing above the recrystallization temperature as much as possible. For example, in the case of Fe-Ni alloys or stainless steel, it is preferably annealed at a temperature above 700°C. Preferably, it is above 750°C or above 800°C. In annealing at less than 700°C, rolling is performed in a state of residual dislocations, so it is easy to introduce dislocations in the final rolling, and the rolling load becomes smaller, but it becomes a high dislocation density state, vacancies are easily consumed, and the PAL will eventually have a short life.
[0106] [Applied to component materials]
[0107] It should be noted that the Fe-Ni alloy foil of the present invention can be used as a material for all parts because it suppresses deformation even when the thickness is thinned. In particular, in electronic devices such as battery materials, the demand for thin alloy foils has increased due to the need for lightweight, high functionality, and high strength, and it is preferably used in these component materials.
[0108] In addition, although it is not applied to the component itself, it can also be applied to the components (parts) used when manufacturing the component. For example, the Fe-Ni alloy foil of the present invention can be applied to the metal mask of OLED. This is because the metal mask of OLED uses Fe-Ni alloy foil for high precision due to its etching properties and low thermal expansion, but in order to further improve the precision, it is required to reduce the thickness and suppress the deformation.
[0109] In the present invention, components (parts) used for manufacturing electronic components are also included in the components, not the electronic components or mechanical components themselves such as metal masks.
[0110] Furthermore, the component having the Fe—Ni alloy foil of the present invention includes not only a component made of the Fe—Ni alloy foil but also a component having a portion made of the Fe—Ni alloy foil.
[0111] Example
[0112] [Test piece]
[0113] A HIP material produced by HIP method using an Fe-Ni alloy ingot adjusted to the composition shown in Table 1 based on Fe-36Ni alloy and a molten material produced by a conventional method were prepared. The remainder of the composition in Table 1 is Fe and impurities.
[0114] First, for HIP parts, the melt (molten alloy) adjusted to the composition shown in Table 1 was made into spherical alloy powder by gas atomization. The obtained alloy powder was classified, and the product under the 300μm sieve was HIP treated to obtain HIP parts. The HIP treatment was carried out in the usual order, and as the HIP treatment conditions, the HIP parts were manufactured at a high temperature and high pressure of 1150℃ and 120MPa for 3 hours. As shown in Table 1, HIP1 and HIP2 were prepared as HIP parts with different compositions.
[0115] On the other hand, as a comparative material, for a continuous casting billet based on the conventional manufacturing method, after solidifying the molten metal adjusted to the component composition shown in Table 1, it was further re-refined by the ESR method (electroslag remelting method) or the VAR method (vacuum arc remelting method), and then a slab was obtained according to the conventional continuous casting method. As shown in Table 1, a smelt 1 and a smelt 2 were prepared as smelting materials with different components.
[0116] [Table 1]
[0117]
[0118] The obtained test pieces were subjected to processing such as rolling and annealing to produce alloy foils. Table 2 shows the processing conditions of the test pieces.
[0119] The test pieces of HIP1 and HIP2 were machined into rectangular shapes with thicknesses of 1mm, 3mm, 10mm, and 50mm to obtain alloy plates. The alloy plate with a thickness of 50mm was hot-rolled to form an alloy plate with a thickness of 3mm. Alloy plates of other thicknesses were not hot-rolled. The alloy plates with thicknesses of 1mm, 3mm, and 10mm thus obtained were cold-rolled to obtain Fe-Ni alloy foils with a final thickness of 30μm (0.030mm). In addition, alloy foils that were intermediately annealed during the cold rolling process and alloy foils that were not intermediately annealed were prepared.
[0120] On the other hand, for the molten material equivalent to the existing manufacturing method, the slab thickness after continuous casting is 250 mm, which is then hot-rolled into an alloy plate with a thickness of 300 μm (0.300 mm), and the final Fe-Ni alloy foil with a thickness of 30 μm (0.030 mm) is obtained through (intermediate) cold rolling, intermediate annealing, and (final) cold rolling.
[0121] The deformation amount of each of the obtained Fe—Ni alloy foils was evaluated by the vertical direction suspension test as described above. Figure 2 An overview of the vertical suspension test is shown in the figure. The alloy foil is cut into a rectangular sheet with a width of 40 mm and a length of 250 mm (cut in such a way that the length direction becomes the rolling direction) as a test piece 1, and it is suspended on a vertical plane 3 of a vertical platform (a platform having a plane (vertical plane) parallel to the vertical direction) 2. The gap amount of the gap 5 between the vertical plane 3 and the test piece 1 is measured, and the maximum value is evaluated as the deformation amount. In this embodiment, a weight of 100 g is hung on the lower end of the test piece to generate a tension 4, and a feeler gauge (not shown) is used to measure the deformation amount. Figure 3 The gap 5 (in the dotted frame in the figure) generated between the test piece 1 and the vertical plane 3 of the vertical platform 2 is shown. The range 6 for measuring the gap 5 is not particularly limited, but the entire width of the vertical plane 3 can be set as the measurement range 6, which is set in this embodiment. Each gap is measured 4 times, and the average is taken as the deformation amount of the gap. The maximum value of the deformation amount of each gap is taken as the deformation amount of the test piece for evaluation.
[0122] Regarding the average positron annihilation lifetime (PAL), as mentioned above, the Fe-Ni alloy foil of each test piece is cut into 10 mm squares, and two groups of three overlapping pieces are prepared. The positron beam source is clamped with three overlapping Fe-Ni alloy foils, and the foil is wrapped and fixed with aluminum foil to prepare a PAL measurement sample. The prepared measurement sample is placed in a measurement device to measure the positron annihilation lifetime (PAL). As a PAL measurement device, a positron annihilation lifetime device manufactured by techno-ap is used. 22Na was used as a positron beam source for evaluation. PALSfit3 developed by Denmark University of Technology was used as the data analysis software. In order to consider the influence of the lifetime of Kapton film (0.3800ps) and epoxy lifetime (1.9044ps), the lifetimes of these films were fixed and the average positron annihilation lifetime was analyzed for the material as a single component.
[0123] Table 2 shows the manufacturing conditions, deformation amount, and PAL (mean positron annihilation lifetime) measurement results of each test piece. Figure 1 The middle figure shows the relationship between the deformation amount shown in Table 2 and PAL. Figure 1 The triangle marks in the figure are comparative examples (melted parts), and the circle marks are examples (HIP parts).
[0124] [Table 2]
[0125]
[0126] From Table 2 and Figure 1 It can be seen that there is a correlation between the average positron annihilation lifetime (PAL) and the deformation amount. When the PAL lifetime is increased, the deformation amount is reduced. Compared with Comparative Example 1, which is equivalent to the conventional product, it can be seen that the PAL of the examples after HIP treatment is 0.150 nsec or more, and it can be confirmed that the deformation amount is smaller than that of Comparative Example 1. In addition, even from the perspective of component composition, when comparing Examples 1 to 6 of HIP 1 with substantially the same alloy elements added and Comparative Example 3 of molten material 2, it can be confirmed that the HIP material has a long PAL and a small deformation amount.
[0127] Industrial Applicability
[0128] The present invention can be used in Fe-Ni alloy foils, and its effect is particularly remarkable when used in ultra-thin Fe-Ni alloy foils having a thickness of 50 μm or less.
[0129] Description of Reference Numerals
[0130] 1 Test piece
[0131] 2 Vertical platform
[0132] 3 Vertical plane
[0133] 4 Tension (direction)
[0134] 5. Gap
[0135] 6 Measurement range
Claims
1. A Fe-Ni alloy foil, characterized in that: The components are as follows in mass %: C: 0 to 0.030%, Si: 0-0.21%, Mn: 0~0.30%, Ni: 30.0~60.0%, Co: 0-5.00%, P: 0.01% or less, S: 0.01% or less, and The rest is Fe and impurities. The plate thickness is 50 μm or less, and the positron annihilation lifetime is 0.150 ns or more.
2. The Fe-Ni alloy foil according to claim 1, The positron annihilation lifetime is 0.150ns to 0.200ns.
3. The Fe-Ni alloy foil according to claim 1 or 2, wherein: The plate thickness is 20 μm or less.
4. A method for producing a Fe-Ni alloy foil, the method for producing a Fe-Ni alloy foil according to claim 1 or 2, characterized in that: include: A process for preparing Fe-Ni alloy powder; A Fe-Ni alloy ingot manufacturing process of manufacturing the Fe-Ni alloy powder into a Fe-Ni alloy ingot by a HIP method; and a rolling process of rolling the Fe-Ni alloy ingot, The composition of the Fe-Ni alloy powder is C: 0-0.030% by mass, Si: 0-0.21%, Mn: 0~0.30%, Ni: 30.0~60.0%, Co: 0-5.00%, P: 0.01% or less, S: 0.01% or less, and The remainder is Fe and impurities.
5. The method for producing the Fe-Ni alloy foil according to claim 4, Furthermore, the rolling process includes at least one annealing process between each rolling pass or after the final rolling.
6. The method for producing the Fe-Ni alloy foil according to claim 4, The plate thickness is 20 μm or less.
7. The method for producing the Fe-Ni alloy foil according to claim 5, The plate thickness is 20 μm or less. 8 . A component comprising the Fe—Ni alloy foil according to claim 1 .
9. The component according to claim 8, The Fe—Ni alloy foil has a thickness of 20 μm or less.
Citation Information
Patent Citations
Stainless steel foil and method for manufacturing same
WO2015122523A1
Metal mask material, method for producing same, and metal mask
WO2020067537A1